1990
DOI: 10.1111/j.1365-2842.1990.tb01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between degree of conversion, filler concentration and mechanical properties of posterior composite resins

Abstract: The degree of conversion, filler concentration and mechanical properties of seven proprietary light-cured posterior composite resins were investigated. The degree of conversion of composites ranged from 43.5-73.8%. The weight fraction of filler that was obtained was in the range 66.4-85.2%. The volume fraction varied from 58.2-74.2%. The mean values of the observed compressive and diametral tensile strengths ranged from 242.3-324.7 MPa and from 39.8-62.6 MPa, respectively. The Knoop hardness numbers ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
0
26

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(179 citation statements)
references
References 21 publications
8
145
0
26
Order By: Relevance
“…This is in agreement with several studies that relate the filler loading to the surface hardness of the resin-based materials [51][52][53][54][55]. V-BF and SDR Bulk fill materials showed the lowest VHN and this could be explained by their low filler loading [56].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with several studies that relate the filler loading to the surface hardness of the resin-based materials [51][52][53][54][55]. V-BF and SDR Bulk fill materials showed the lowest VHN and this could be explained by their low filler loading [56].…”
Section: Discussionsupporting
confidence: 92%
“…That was in accordance with other studies, as they found very low correlation between the filler loading and mechanical properties of dental resin-composites [25,67]. On the other hand, Chung et al found a clear correlation between the filler loading and the surface hardness and DTS of group of resincomposites [54,68].…”
Section: Discussionsupporting
confidence: 91%
“…As expected, the CS value did not correlate with all the mechanical properties that were investigated in the present study (Table 4). The finding of lack of correlation between the CS value and the other mechanical parameters was consistent with that in prior reports 16,24) . On the other hand, in this study, the DTS value showed a significant correlation with the FM value (r=0.64) and the V f (r=0.71).…”
Section: Correlation Between the Mechanical Propertiessupporting
confidence: 92%
“…In a similar way, the mean CS value correlated with the V f value in the experimental composites 11,47) . However, either of the group comprising for a wide range of early and contemporary resin composites did not show any significant correlation between the filler fraction and the mean CS value 16,24,38,58) .…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation